2018
DOI: 10.1002/ppp.1986
|View full text |Cite
|
Sign up to set email alerts
|

Thermokarst pond dynamics in subarctic environment monitoring with radar remote sensing

Abstract: Permafrost degradation can be monitored through changes in the surface area and depth of thermokarst ponds. Radar remote sensing allows for discrimination of thermokarst ponds of different depths across large areas because different water depths produce different ice regimes in winter. In this study, patterns in the spatial distribution of ice‐cover regimes of thermokarst ponds in a typical discontinuous permafrost region are first revealed. Correlations of these ice‐cover regimes with the permafrost degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Increasing trends in the surface of lakes were predominantly observed in the continuous permafrost zone from Siberia 81,83,84 . Wang et al 85 reported a substantial increase in the number of thermokarst ponds in north Canada but with an insignificant increase in their total surface area. In addition, in the continuous permafrost zone in Mongolia, thermokarst lakes and ponds expanded in number and water‐surface area by 21 and 7%, respectively 82 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing trends in the surface of lakes were predominantly observed in the continuous permafrost zone from Siberia 81,83,84 . Wang et al 85 reported a substantial increase in the number of thermokarst ponds in north Canada but with an insignificant increase in their total surface area. In addition, in the continuous permafrost zone in Mongolia, thermokarst lakes and ponds expanded in number and water‐surface area by 21 and 7%, respectively 82 .…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of permafrost has major implications for the environment. A variety of related landscape features and processes are visualized by the infographic in Figure 1, such as emerging greenhouse gas emissions [33][34][35][36][37][38], coastal erosion [39][40][41][42], amplified surface deformation rates due to frost heave or thaw settlement [43][44][45][46], landslides [47][48][49], increasing depths of the active layer [50][51][52], thermokarst lakes and ponds [53][54][55][56], wild fires [57][58][59], changing rock glacier kinematics [47,60,61], patterned ground [62,63], and thaw slump activities [64][65][66]. The reorganization of hydrological flowpaths, soil carbon stocks and vegetation composition are also consequences of thawing permafrost [67].…”
Section: Definition Of Permafrostmentioning
confidence: 99%
“…To validate PALSAR and SMAP F/T monitoring results, we installed 13 Hobo-logger sensors at ~5 cm depth to measure continuously the soil moisture and soil temperature near Umiujaq (Bernier et al 2019). The soil is classified as thawed when the soil temperature recorded by the Hobosensor at ~5 cm depth is higher than 0°C and frozen when the soil temperature is lower than 0°C (Wang et al 2018;Touati et al 2019). 2014, 19, and23 andDecember 3, 8, 12, and17, 2016, were available.…”
Section: Palsar F/t Mappingmentioning
confidence: 99%
“…Under the frozen cold conditions, the backscattering coefficient decrease due to the decrease of the soil dielectric constant (Baghdadi et al 2018). Otherwise, the Differential Synthetic Aperture Radar Interferometry (D-InSAR) has been used to monitor soil surface deformation caused by freeze thaw transition and to estimate active layer depth in permafrost and discontinuous permafrost regions (Daout et al 2017;Wang et al 2017Wang et al , 2018Chen et al 2020).…”
Section: Introductionmentioning
confidence: 99%